Hybrid surface‐acoustic‐wave/microstrip signal‐interference bandpass filters. Issue 4 (1st March 2016) - Gómez‐García, Roberto; Psychogiou, Dimitra; Loeches‐Sánchez, Raúl; Peroulis, Dimitrios
Abstract : Radio‐frequency (RF) design techniques for the development of signal‐interference microwave bandpass filters (BPFs) with hybridised microstrip and surface‐acoustic‐wave (SAW) elements are reported. They make use of two original types of transversal filtering sections (TFSs) with embedded one‐port SAW resonators. The SAW resonators operate either as non‐resonating nodes or as an in‐band SAW BPF in their bi‐path circuit topologies. These new TFS approaches extend the suitability of signal‐interference BPFs to small‐fractional‐bandwidth (FBW) applications, while offering significant advantages in terms of filtering selectivity and occupied circuit size when compared to traditional solutions for narrow‐to‐moderate/wide‐band specifications. Broader FBWs than those attainable through most of the available all‐acoustic‐wave BPF configurations are also feasible with them. Moreover, a single type of SAW device is employed in the entire BPF structure, which results in a practical benefit regarding robustness to deviations in the prototype fabrication and assembly processes. The proposed filter design concepts are experimentally verified through the fabrication in microstrip technology and characterisation of two multi‐TFS‐series‐cascade‐based high‐order BPF prototypes with very‐narrow and moderate FBWs.